2014
DOI: 10.1155/2014/483813
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Assisted Alkali Pretreatment of Rice Straw for Enhancing Enzymatic Digestibility

Abstract: Rapid industrialization, increasing energy demand, and climate change are the conditions that forced the researchers to develop a clean, efficient, renewable, and sustainable source of energy which has a potential to replace fossil fuels. Ethanol is one of the attractive and suitable renewable energy resources. In present study, effectiveness of microwave pretreatment in combination with sodium hydroxide (NaOH) for increasing enzymatic hydrolysis of rice straw has been investigated and under optimum conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 39 publications
6
22
0
Order By: Relevance
“…The results suggested that microwave power played a major role in variations of glucose yield. Specifically, high microwave power, given low NaOH concentration, effectively degraded lignin and increased enzymatic accessibility, consistent with Kamalini, Muthusamy, Ramapriya, Muthusamy, and Pugazhendhi () and Singh, Tiwari, Srivastava, and Shukla ().…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The results suggested that microwave power played a major role in variations of glucose yield. Specifically, high microwave power, given low NaOH concentration, effectively degraded lignin and increased enzymatic accessibility, consistent with Kamalini, Muthusamy, Ramapriya, Muthusamy, and Pugazhendhi () and Singh, Tiwari, Srivastava, and Shukla ().…”
Section: Resultssupporting
confidence: 79%
“…Aqueous NaOH also increased the cleavage of intermolecular ester bonds crosslinking lignin and other components such as hemicelluloses. Similar increases in CrI were reported for MAP‐treated cassava stems (Table ) and other lignocelluloses (Boonsombuti et al, ; Singh et al, ; Velmurugan & Muthukumar, ; Wanitwattanarumlug, Luengnaruemitchai, & Wongkasemjit, ). It could be concluded that increased CrI led to enhanced enzyme digestibility.…”
Section: Resultssupporting
confidence: 78%
“…A pretreatment with a microwave oven at a frequency of 2.45 GHz and with a wattage of 950 Watt with varied times and rice straw powder sizes showed a highly significant increase in cellulose content and a highly significant reduction in lignin and hemicelluloses content [2]. Combining microwave pretreatment with NaOH can increase the glucose content and reduce the lignin and hemicellulose content [21]. A pretreatment with a microwave oven combined with NaOH increased the cellulose content of banana stems compared to other treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave pretreatment with an acid has advantages at the reaction conditions such as corrosion, high temperatures, and economically cheaper. If the concentration of acid/alkali is increased, the glucose content also increases [21][22] reported that pretreatment with microwave combined with distilled water, NaOH and H 2 SO 4 at a temperature ranging from 130 to 200 o C on miscanthus showed H 2 SO 4 resulted in maximum glucose content at a temperature of 180 o C. At 200 o C, however, the glucose content significantly decreased. The mechanism of how a microwave increases the chemical reaction has yet to elucidate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation